2021
DOI: 10.1126/science.abg6105
|View full text |Cite
|
Sign up to set email alerts
|

Neutralization of SARS-CoV-2 lineage B.1.1.7 pseudovirus by BNT162b2 vaccine–elicited human sera

Abstract: Recently, a new SARS-CoV-2 lineage called B.1.1.7 (variant of concern: VOC 202012/01) emerged in the United Kingdom that was reported to spread more efficiently and faster than other strains. This variant has an unusually large number of mutations with 10 amino acid changes in the spike protein, raising concerns that its recognition by neutralizing antibodies may be affected. Here, we tested SARS-CoV-2-S pseudoviruses bearing either the Wuhan reference strain or the B.1.1.7 lineage spike protein with sera of 4… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
384
0
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 506 publications
(409 citation statements)
references
References 11 publications
22
384
0
3
Order By: Relevance
“…This is unsurprising given that there is no observed increase in reinfection reported with B.1.1.7 nor was there high seroprevalence in the UK during the emergence of this variant. Our finding is supported by many studies using B.1.1.7 viruses and PV which show either no reduction or a modest reduction in polyclonal serum titres (Collier et al, 2021;Diamond et al, 2021;Hu et al, 2021;Muik et al, 2021;Rees-Spear C et al, 2021;Wang et al, 2021;Wu et al, 2021). There is some evidence of heterogeneity of responses and neutralising titres for some individuals with initially low responses against WT virus can drop below limits of detection against the B.1.1.7 variant (Skelly et al, 2021).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This is unsurprising given that there is no observed increase in reinfection reported with B.1.1.7 nor was there high seroprevalence in the UK during the emergence of this variant. Our finding is supported by many studies using B.1.1.7 viruses and PV which show either no reduction or a modest reduction in polyclonal serum titres (Collier et al, 2021;Diamond et al, 2021;Hu et al, 2021;Muik et al, 2021;Rees-Spear C et al, 2021;Wang et al, 2021;Wu et al, 2021). There is some evidence of heterogeneity of responses and neutralising titres for some individuals with initially low responses against WT virus can drop below limits of detection against the B.1.1.7 variant (Skelly et al, 2021).…”
Section: Discussionsupporting
confidence: 83%
“…In an intense burst of research around this question, convalescent and post-vaccination sera have been used in neutralisation assays with B.1.1.7 live virus isolated from infected patients, recombinant viruses generated by reverse genetics and virus pseudotypes (PV) with some or all of the B.1.1.7 mutations in S, but results have been inconsistent. In some studies, PV bearing B.1.1.7 and wildtype S showed equivalent (<2-fold) neutralisation by convalescent sera (Collier et al, 2021;Rees-Spear C et al, 2021) or sera raised against vaccines (Muik et al, 2021;Wu et al, 2021). However, other studies found a modest decreased susceptibility (up to 4-fold) of B.1.1.7 PV to convalescent sera (Hu et al, 2021;Wang et al, 2021) or vaccine sera (Collier et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, while the B.1.1.7 variant may be more transmissible, it was equally as sensitive to vaccine-induced serum neutralization as the predominant circulating SARS-CoV-2 D614G strain. Importantly, cross-reactive RBD-scNP immune sera and S-2P mRNA-LNP immune sera bound equally as well to spike ectodomain molecules with South African B1.351, Brazilian P.1 and UK B.1.1.7 RBD mutations, and are compatible with the recent demonstration that current COVID-19 vaccines have efficacy, albeit reduced, against the UK and South African SARS-CoV-2 variants 5055 .…”
Section: Mainsupporting
confidence: 81%
“…One major concern is the possibility that a profoundly mutated spike protein may alter the recognition by neutralizing antibodies, raising concerns about the protective ability of the recently issued vaccines that are based on original spike protein sequences. The evidence provided in the present study, according to a recent report [13], indicates that the VOC202012/01 variant is sensitive to the neutralizing activity of antibodies produced by patients in response to previously circulating viral strains, and the neutralizing titers are identical to those established by using as virus challenge a different strain that was isolated several months ago and is used nationwide to establish the neutralization titer of hyperimmune convalescent plasma preparations in Italy. These data are reassuring, in that all those who have overcome the disease and have produced good levels of protective antibodies may be protected against a possible reinfection sustained by an even distant SARS-CoV-2 strain.…”
Section: Discussionsupporting
confidence: 72%